2017
DOI: 10.1016/j.jid.2016.09.031
|View full text |Cite
|
Sign up to set email alerts
|

CARD14-Mediated Activation of Paracaspase MALT1 in Keratinocytes: Implications for Psoriasis

Abstract: Mutations in caspase recruitment domain-containing protein 14(CARD14) have been linked to susceptibility to psoriasis. CARD14 is an intracellular scaffold protein that regulates proinflammatory gene expression. Recent studies have offered novel insights into the mechanisms of CARD14-mediated signaling in keratinocytes and the molecular impact of psoriasis-associated CARD14 mutations. CARD14 forms a signaling complex with BCL10 and the paracaspase MALT1, and this process is enhanced upon pathogenic CARD14 mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 69 publications
1
27
0
Order By: Relevance
“…Interestingly, activating mutations in the CARMA2-encoding gene CARD14 have been found to be associated with development of psoriasis, an inflammatory skin disease, in human patients (122, 123). Since then, an increasing number of studies have reported genetic mutations in CARD14 associated to psoriasis diseases (124). Some of the CARD14 mutations found in patients were shown to enhance NF-κB activation and promote secretion of CCL20 and IL-8, two chemokines known to be associated with psoriasis (123, 124).…”
Section: Malt1 Deregulation Is Associated With Allergy Inflammatory mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, activating mutations in the CARMA2-encoding gene CARD14 have been found to be associated with development of psoriasis, an inflammatory skin disease, in human patients (122, 123). Since then, an increasing number of studies have reported genetic mutations in CARD14 associated to psoriasis diseases (124). Some of the CARD14 mutations found in patients were shown to enhance NF-κB activation and promote secretion of CCL20 and IL-8, two chemokines known to be associated with psoriasis (123, 124).…”
Section: Malt1 Deregulation Is Associated With Allergy Inflammatory mentioning
confidence: 99%
“…Since then, an increasing number of studies have reported genetic mutations in CARD14 associated to psoriasis diseases (124). Some of the CARD14 mutations found in patients were shown to enhance NF-κB activation and promote secretion of CCL20 and IL-8, two chemokines known to be associated with psoriasis (123, 124). Similar to CARD11 mutations associated with lymphoid malignancies, CARD14 mutations were mostly found in the CC region.…”
Section: Malt1 Deregulation Is Associated With Allergy Inflammatory mentioning
confidence: 99%
See 1 more Smart Citation
“…CARD14 encodes a member of the membrane‐associated guanylate kinase family, and falls within PSORS2 , the psoriasis susceptibility 2 locus . CARD14 is known to activate NF‐κB, while increasing the expression of inflammatory factors including tumor necrosis factor alpha (TNFα), interleukin‐17 (IL‐17), chemokine ligand 8 (CXCL‐8), and interleukin‐36γ (IL‐36γ) . These are canonical pathways implicated in psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…IB, immunoblot; WT, wild type. of affecting T-cell and keratinocyte function (downstream of CARD11 and CARD14, respectively) (Van Nuffel et al, 2017). Targeting CARD14 directly, however, may permit the development of more specific therapies with decreased adverse effect profiles, and this merits further investigation into understanding CARD14 biology.…”
Section: Discussionmentioning
confidence: 99%